Heat Transfer Performance and Flow Characteristics of a Heat Exchange Tube with Isosceles Trapezoidal Winglet Longitudinal Vortex Generators - Lin Liu; Zhichun Ni; Haoyuan Tang; Hui Xu; Bingyun Jiang (Energies)
The thermal-hydraulic performance of circular heat transfer tubes equipped with isosceles trapezoidal winglet longitudinal vortex generators (ITWL-VGs) was investigated through integrated experimental and numerical approaches. Experimental studies were conducted that focused on the effects of key parameters: (1) the ITW quantity (n = 4, 6, 8); (2) the attack angle (α = 0°, 15°, 30°, 45°); and (3) four distinct VG arrangements. Numerical simulations employing multi-physical field analysis elucidated the underlying heat transfer enhancement mechanisms. The numerical simulations demonstrated excellent agreement with the experimental measurements. The results indicated that uniformly distributed ITWL-VGs with suitable angles of attack (α) significantly enhanced the thermal performance. Increasing the number of ITWs (N) generated additional longitudinal vortices, intensifying fluid mixing and heat transfer enhancement, thereby improving the PEC value. All the Nusselt number (Nu), friction factor (f) and PEC values exhibited positive correlations with the α and the spacing (LP), respectively. Within the scope of this study, the α should not be less than 30°. In addition, an optimal value should be used for the LP. The maximum PEC value was 1.27. These findings conclusively demonstrated the significant heat transfer enhancement capabilities of ITWL-VGs.